Mísera princesa destronada: crime e ordem pública em pelotas (1902-1928) - Gouvêa, Melissa Xavier (2015)
This dissertation examines the social history of crime and criminals in the first decades of the twentieth century, in the city of Pelotas, state of Rio Grande do Sul. In the same way, the work retraces the changes and procedures of Pelotas policing, between 1902 and 1928, to understand that during the studied years occurred more effective control in different urban areas - and on certain portion of the population - especially after the reorganization of the municipal police (1902) and the creation of the Bureau of Identification (1915). From researched sources (press, police statistics and official documents), it demonstrates that the discourse on surveillance and prevention of criminal practices is accompanied by the progressive discourse, linked to the development plans of Pelotas. The crimes were, particularly, disorder, vagrancy, drunkenness and prostitution, and all such violations of public order were accused of preventing local progress. Therefore, in order to demonstrate traces of urban violence, the research was divided into three themes: the context of the city of Pelotas in the early twentieth century, the creation of a new kind of Republican policing at the time and, finally, the description of prisoners and the major crimes occurred in Pelotas. In short, this work makes possible to understand the ways of crime prevention and also demonstrates the crimes and marginal agents, barely present in the official history of the city of Pelotas.